Are There Differences in the Health-Socioeconomic Status Relationship over the Life Cycle? Evidence from Germany - Keith A. Bender; Steffen Habermalz (Institute for the Study of Labor (IZA), 2005)
Most research on the relationship between health and socioeconomic status (SES) controls for changing age or investigates the relationship for a particular age range. This paper, however, examines changes in the relationship across ages, as well as controls for potential endogeneity in the health-SES relationship. Using data from German Socio Economic Panel, we find that the health-SES relationship does vary across the life cycle and that endogeneity is an important influence on the relationship. We also find tentative evidence that universal access to health care reduces the impact of income on self-reported health satisfaction.
Keywords: I12; C13; I0; J60; J0; 330; health; socioeconomic status; endogeneity; life cycle; Germany